Didymosphenia geminata (Lyngbye) M. Schmidt y Gomphoneis minuta (Stone) Kociolek & Stoermer (Bacillariophyta), especies presentes en ríos de la VIII Región, Chile, formadoras de proliferaciones con aspecto muy similar - Basualto, Silvia; Rivera, Patricio; Cruces, Fabiola; Ector, Luc; Ascencio, Enrique (Gayana Botánica, 2016)
A light brown colored massive algal proliferation found in a large area of Rio Laja, Chile was studied. The bloom was produced by Gomphoneis minuta, a gomphonemoid diatom forming large branched stalks attached to submerged rocks. At first glance and on account the macroscopic appearance, this type of proliferation could be confused with that of Didymosphenia geminata. Considering its massive presence in Rio Laja and increased distribution in Chilean waters, as well is occurring in many European and American rivers, we postulate that G. minuta could be a nuisance species in Chilean rivers, and similar to D. geminata, it must be controlled to verify its propagation in the country.